2001
DOI: 10.1002/yea.805
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the Hansenula polymorphaFLD1 gene encoding formaldehyde dehydrogenase

Abstract: Glutathione-dependent formaldehyde dehydrogenase (FLD) is a key enzyme required for the catabolism of methanol as a carbon source and certain primary amines, such as methylamine as nitrogen sources in methylotrophic yeasts. Here we describe the molecular characterization of the FLD1 gene from the yeast Hansenula polymorpha. Unlike the recently described Pichia pastoris homologue, the H. polymorpha gene does not contain an intron. The predicted FLD1 product (Fld1p) is a protein of 380 amino acids (ca. 41 kDa) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
2
18
0
1
Order By: Relevance
“…Some physico-chemical characteristics of the purified FdDH are shown in The molecular mass of the FdDH subunit, estimated by SDS-electrophoresis, was shown to be approximately 40 kDa, similar to the 41 kDa found for C. boidinii (Melissis et al, 2001). It was reported that the predicted FLD1 gene product (Fld1p) is a protein of 380 amino acids (Baerends et al, 2002). Taking into account, that the M of the native enzyme from various methanol-utilizing yeasts were estimated to be from 80 to 85 kDa, isolated thermostable, NAD + -and GSH-dependent FdDH can be assumed to be dimeric.…”
Section: Fddh Purification and Characterizationsupporting
confidence: 54%
See 1 more Smart Citation
“…Some physico-chemical characteristics of the purified FdDH are shown in The molecular mass of the FdDH subunit, estimated by SDS-electrophoresis, was shown to be approximately 40 kDa, similar to the 41 kDa found for C. boidinii (Melissis et al, 2001). It was reported that the predicted FLD1 gene product (Fld1p) is a protein of 380 amino acids (Baerends et al, 2002). Taking into account, that the M of the native enzyme from various methanol-utilizing yeasts were estimated to be from 80 to 85 kDa, isolated thermostable, NAD + -and GSH-dependent FdDH can be assumed to be dimeric.…”
Section: Fddh Purification and Characterizationsupporting
confidence: 54%
“…The toxicity of FA in batch assays, using volatile fatty acids as co-substrates and the continuous anaerobic treatment of wastewaters containing FA in upflow anaerobic sludge blanket reactors was investigated (Vidal et al, 1999). The kinetic process of FA biodegradation in a biofilter packed with a mixture of compost, vermiculite powder and ceramic particles was studied by Xu et al (2010 (Baerends et al, 2002) was inserted into the integrative plasmid pYT1 (Demkiv et al, 2005) containing the LEU2 gene of Saccharomyces cerevisiae (as a selective marker). The constructed vector was used for multi-copy integration of the target gene into the genome of H. рolymorpha by transformation of leu 1-1 (Demkiv et al, 2005) and leu 2-2 recipient cells (both leu alleles are complemented by S. cerevisiae gene LEU2).…”
Section: Microbial Methanol and Formaldehyde Biodegradation In Wastewmentioning
confidence: 99%
“…Formaldehyde was efficiently coutilized by an engineered S. cerevisiae strain that expresses H. polymorpha genes encoding Fld and Fmd (3,19). Transcriptome analysis played a key role in identifying a biotin limitation in the initial fermentation experiments with formaldehyde coutilization by chemostat cultures.…”
Section: Discussionmentioning
confidence: 99%
“…2). This plasmid also carried the H. polymorphaFLD1 gene under control of a truncated constitutive promoter from the glyceraldehyde-3-phosphate dehydrogenase gene (GAP) (Baerends et al, 2002, Sohn et al, 1999. Utilization of this construct allowed us to efficiently screen for pKO13 multicopy integrants as clones resistant to elevated concentrations of extracellular formaldehyde (Fig.…”
Section: Production Of Secreted Mini-proinsulin (Mpi) In An Eao Mutantmentioning
confidence: 99%
“…BamHI/BglII fragment from the latter plasmid, harboring the entire MPI expression cassette, was ligated into BamHI digested vector pKO12, derivative of pGLG61 multiple integration vector (Sohn et al, 1999), resulting in plasmid pKO13. pKO12 carries an alternative selection marker, the H. polymorpha formaldehyde dehydrogenase (FLD1) gene (Baerends et al, 2002), placed under the shortened GAP promoter instead of the APH gene. HpFLD1 ORF was isolated from the plasmid pYG2 (Shen et al, 1998) as EcoRI/SmaI flanked PCR product with primers OL42 (5 0 -TGGAATTCATGTCTACTGTCGGAA-3 0 ) and OL43 (5 0 -TTCCCGGGTTATTATGGTAGTTGT-3 0 ), and ligated into EcoRI/StuI digested pGLG61.…”
Section: Construction Of the Mpi Expression Vector Pko13mentioning
confidence: 99%